Vision Rehabilitation in Patients with Age-related Macular Degeneration. (March 2014) - Amore, Filippo M.; Fortini, Stefania; Silvestri, Valeria; Sulfaro, Marco; Pacifici, Alessia; Turco, Simona
Background: The aim of this study was to investigate the rehabilitative process and visual rehabilitation outcomes in patients with central vision loss due to age-related macular degeneration (AMD). Methods: Ninety-five subjects with AMD selected from the attendees of the National Centre of Services and Research for the Prevention of Blindness and Rehabilitation of Low Vision Patients—International Agency for Prevention of Blindness—IAPB Italia Onlus, were evaluated for this retrospective study. Low vision examination included psychological counseling, best corrected visual acuity (BCVA), near visual acuity, Pelli-Robson contrast sensitivity, and fixation stability analysis. Once the clinical assessment was completed, patients attended a low-vision rehabilitative pathway based on visual stimulation, devices training and, if needed, psychological support. Required magnification and reading speed were also evaluated. Results: For the whole sample, the mean BCVA of the better eye was 0.7 (±0.2) LogMAR and of the worse eye was 1 (±0.2) LogMAR. Restoring reading ability was the most important focus for the patients examined as it was requested by 85% of the whole sample. Mean power of optical magnifying aids for near activities was 10.6 (±9.1) positive spherical diopters. Mean reading speed for the whole sample was 33.1 (±18.2) words per minute (wpm) before visual rehabilitation sessions and increased to 55.2 (±33.1) wpm after visual rehabilitation path. To cope with distance difficulties, 78 distance refractive correction, 10 Galilean telescopes, and 7 Keplerian telescopes were prescribed. For intermediate distance activities, 22 compensation lenses and 10 Galilean telescopes were suggested. Moreover, PC magnifier softwares were prescribed to nine patients. Sixty-five polarized medical filters were prescribed to reduce glare of sunlight. Because of unstable fixation in their better eye (32.3% (±19.7) within 2° circle and 54.8% (±22.9) within 4° circle) and visual acuity < 1.2 LogMAR in the fellow eye, 38 subjects, before starting the devices training sessions, attended a bio-feedback rehabilitation session with flickering pattern stimulus. In these subjects, fixation stability increased significantly to 75.6 (±14.9) within 2° and 89.4 (±19.5) within 4° ( P < 0.05), respectively. Conclusions: Attending a customized low-vision intervention based on a multidisciplinary approach seems to be effective for improving visual functions in AMD. Both optical/electronic magnifiers and specific visual stimulation program can enhance visual performances.